Development of an Encyclopedia of Closed Seed Plants (Angiosperms) in the Madrasah Technonatura Yogyakarta Area As a Science Learning Resource for MI and MTS Students - Najah, Khoirun (Proceeding International Conference on Religion, Science and Education, 2025)
Development of an Encyclopedia of Closed Seed Plants. The high diversity of plant species at Madrasah Technonatura Yogyakarta is a local potential that can be utilized as a learning resource in the science learning process. This research aims to determine the diversity of types of closed seed plants in the Madrasah Technonatura Yogyakarta area and develop an encyclopedia of several types of closed seed plants and determine the quality of the products developed. This research is a type of R & D (Research and Development) research. This research uses an exploratory method. Development research method with the ADDIE model (analysis, design, development, implementation, evaluation). The final result of the research is printed media in the form of an encyclopedia of closed seed plants. Products are assessed using an assessment instrument in the form of a checklist questionnaire sheet. The product was assessed by 1 material expert, 1 media expert, 3 peer reviewers, 1 science teacher, and 10 responses from MTS Technonatura level 7 students and 7 MI Technonatura level 3 students. The data obtained was then analyzed descriptively qualitatively and quantitatively. The results of research on the encyclopedia of closed seed plants by material experts received a percentage of 90% in the very good category, media experts 95% in the very good category, peer reviewers 96% in the very good category, science teachers 95% in the very good category, and students 95% in the very good category. Thus, it can be concluded that the encyclopedia of closed seed plants that has been developed is suitable for use as a science learning resource for MI and MTS students. (Angiosperms) in the Madrasah Technonatura Yogyakarta Area As a Science Learning Resource for MI and MTS Students.